Quick butt welding of steel sheets using the high-speed laser cladding method - Li, Yongjian; Liu, Xiaoting; Yan, Shixing; He, Peng (Frontiers in Materials, 2022)
Laser butt welding of thin steel sheets without filler material was widely used in many industrial fields. However, it was very difficult to focus the small laser spot on the narrow gap between the sheets during the laser butt welding process. In this study, a new method to weld thin steel sheets using a high-speed laser cladding technique is proposed. Stainless steel sheets with a thickness of 0.5 mm were welded using the high-speed laser cladding process. The results illustrated that good weld joints could be obtained without obvious cracks and pores in most of the specimens. The joints were well formed even if the sheets were not spliced together entirely. The average tensile strength of the specimens was about 500 MPa, which is almost the same as that of the substrate. The results also showed that most of the failures did not happen in the welding region, which could be concluded that the strength of joints was higher than that of the substrate. The microstructure was determined using an optical microscope (OM) and scanning electron microscope (SEM). The results showed that it may be a good choice to use the high-speed laser cladding technique for butt welding of stainless steel sheets.